2009
DOI: 10.1254/jphs.09112fp
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Telmisartan on Right Ventricular Remodeling Induced by Monocrotaline in Rats

Abstract: Abstract. The present study investigated whether telmisartan, an angiotensin II type 1 receptor antagonist, has cardioprotective effects on monocrotaline-induced right ventricular (RV) remodeling in rats. Six-week-old male Wistar rats were divided into control group (CONT), monocrotaline (60 mg/ kg, i.p.)-treated group (MCT), monocrotaline (60 mg/ kg, i.p.) + telmisartan (3 mg/kg per day, p.o.)-treated group (MCT+TEL), and telmisartan (3 mg/kg per day, p.o.) alonetreated group (TEL). Hearts were excised after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 31 publications
5
39
1
Order By: Relevance
“…11,12) In the present study, captopril and telmisartan could not suppress isoprenaline-induced myocardial fibrosis and MMPs expressions. There are several reasons for this difference.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…11,12) In the present study, captopril and telmisartan could not suppress isoprenaline-induced myocardial fibrosis and MMPs expressions. There are several reasons for this difference.…”
Section: Discussioncontrasting
confidence: 49%
“…12) Briefly, LV tissues were homogenized in lysis buffer (20 mM Tris-HCl pH 7.5, 150 mM NaCl, 1 mM ethylenediaminetetraacetic acid (EDTA)-2Na, 1 mM ethylene glycol bis(2-aminoethylether)-N,N,NЈ,NЈ-tetraacetic acid (EGTA), 1% Triton, 2.5 mM sodium pyrophosphate, 1 mM b-glycerophosphate, 1 mM Na 3 VO 4 , 1 mg/ml leupeptin; Cell Signaling Technology Inc., Danvers, MA, U.S.A.) containing 1% protease inhibitor cocktail (Nacalai Tesque Inc.) and centrifuged. The supernatant was used for Western blotting.…”
mentioning
confidence: 99%
“…Pre-clinical studies using different models of PAH and right heart failure, however confirmed that the use of ACE inhibitors or angiotensin blockers significantly reduces RV remodelling and improves cardiac function and/or survival [66][67][68][69]. We conclude that in PAH, pharmacological interference in RAAS could (partially) reverse pulmonary and cardiac remodelling, which warrants a prospective controlled clinical study of the effects of ACE inhibitors, angiotensin blockers and/or aldosterone antagonists.…”
Section: Renin-angiotensin-aldosterone Systemmentioning
confidence: 61%
“…[8][9][10] A total of 26 rats aged 10-weeks weighing 310 -360 g were randomly assigned to two groups. RVHF rats (n = 14) received a 60 mg/ kg subcutaneous injection of MCT and the control rats (n = 12) a subcutaneous injection of vehicle.…”
Section: Methodsmentioning
confidence: 99%